2021
DOI: 10.1021/jacs.1c04847
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanism and Energetics of Decomposition of Tetrakis(1,3-dimethyltetrazol-5-imidoperchloratomanganese(II)) from Quantum-Mechanics-based Reactive Dynamics

Abstract: Energetic materials (EMs) are central to construction, space exploration, and defense, but over the past 100 years, their capabilities have improved only minimally as they approach the CHNO energetic ceiling, the maximum energy density possible for EMs based on molecular carbon–hydrogen–nitrogen–oxygen compounds. To breach this ceiling, we experimentally explored redox-frustrated hybrid energetic materials (RFH EMs) in which metal atoms covalently connect a strongly reducing fuel ligand (e.g., tetrazole) to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…The Goddard group pioneered the use of QM-MD pyrolysis simulations to determine the Chapman–Jouguet conditions of energetic materials (RDX, HMX, and CL-20) and accurately predicted the detonation properties at 150 ps. These studies correctly predicted the initial decomposition steps in these materials in simulations of less than 20 ps. Previously, our QM-MD simulations of Mn 4 (μ 3 -NTzMe 2 ) 4 (ClO 4 ) 4 pyrolysis (using the PBE-D3 44–46 functional with spin-polarized GGA to allow unrestricted spin change in the reactions) revealed that starting with the ferromagnetic ground-state coupling between the high-spin manganese centers of the tetranuclear heterocubane cluster and heating it to 2000 K leads to spin flips as the reaction initiate to transfer oxygen atom from perchlorate to manganese . These oxygen atom transfer events decrease the quantum spin of oxidized manganese ions, leading to antiferromagnetic coupling via superexchange across the bridging oxide ligands.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…The Goddard group pioneered the use of QM-MD pyrolysis simulations to determine the Chapman–Jouguet conditions of energetic materials (RDX, HMX, and CL-20) and accurately predicted the detonation properties at 150 ps. These studies correctly predicted the initial decomposition steps in these materials in simulations of less than 20 ps. Previously, our QM-MD simulations of Mn 4 (μ 3 -NTzMe 2 ) 4 (ClO 4 ) 4 pyrolysis (using the PBE-D3 44–46 functional with spin-polarized GGA to allow unrestricted spin change in the reactions) revealed that starting with the ferromagnetic ground-state coupling between the high-spin manganese centers of the tetranuclear heterocubane cluster and heating it to 2000 K leads to spin flips as the reaction initiate to transfer oxygen atom from perchlorate to manganese . These oxygen atom transfer events decrease the quantum spin of oxidized manganese ions, leading to antiferromagnetic coupling via superexchange across the bridging oxide ligands.…”
Section: Resultssupporting
confidence: 55%
“…47−51 Previously, our QM-MD simulations of Mn 4 (μ 3 -NTzMe 2 ) 4 (ClO 4 ) 4 pyrolysis (using the PBE-D3 44−4644−46 functional with spin-polarized GGA to allow unrestricted spin change in the reactions) revealed that starting with the ferromagnetic ground-state coupling between the high-spin manganese centers of the tetranuclear heterocubane cluster and heating it to 2000 K leads to spin flips as the reaction initiate to transfer oxygen atom from perchlorate to manganese. 32 These oxygen atom transfer events decrease the quantum spin of oxidized manganese ions, leading to antiferromagnetic coupling via superexchange across the bridging oxide ligands. In this report, our QM-MD simulations on the dimethyl analogue of 1, hexanuclear cluster Mn 6 (μ 3 -NTzMe 2 ) 6 (ClO 4 ) 6 (2), show a similar decrease in overall spin as the reaction proceeds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, theoretical calculations have become a common part of energetic materials research. 4–6 In the case of DFT and AIMD methods, which are considered to be able to accurately describe atoms and electrons, these methods have been used in various fields of energetic materials research, such as intermolecular interactions between explosives, 7–10 impact behavior of plastic bonded explosives (PBX), 11 thermal decomposition of explosive molecules or crystal, 12–15 and crystal structure. 16 These research methods have been proven to be effective and reliable, and can even obtain theories that are difficult to be achieved by experiments alone, which will provide guidance for the design and understanding of the internal mechanism of energetic materials in the future.…”
Section: Introductionmentioning
confidence: 99%